Counseling Guidance From Islamic Perspective, An Ontological View - Dadang Hamdan Iskandar; Widhya Nusantari; Imas Kania Rahman; Abdul Hayyie Alkattani (Tasfiyah: Jurnal Pemikiran Islam, 2022)
Expanding the definition of Counseling guidance in Islam is not easy, moreover, the nature of counseling guidance in Islam is the integration of religion, theory, and e intersection with the reality of the surrounding actors. In historical light, the difference between Islamic counseling and counseling, in general, is in the possibility of influencing or being influenced. The purpose of this study is to develop the definition of counseling guidance in Islam, a study of Islamic and conventional philosophical thought patterns, and the dynamics of a comprehensive formulation effort. Research using literature (library research). This type of research includes a qualitative description in the literature and sources and or recent findings regarding counseling guidance. The nature of this literature research is a critical and historical study. Data collection in the form of symbolic verbal. The results showed that the formulation of the definition of counseling guidance of Islam has shown firmness on the mission of Islam. The elements of the definition in Counseling guidance of Islam, at least include: (1) services that are proactive, not apathetic or passive, (2) carried out by experts, (3) carried out to individuals, both in individual and group and mass counseling, (4) in the form of advice, support, and advice in accordance with the religious rules of the Qur'an, Sunnah and their derivatives, (5) aimed at self-development, preventing blasphemy and solving problems so that individuals can optimize their potential, (6) paying attention to physical, spiritual and environmental aspects, and ( 7) accomplish happiness in the existence of this world and the hereafter